Comparison of Wear Properties of AISI D3 and O1 Steel with the Same Hardness - Singh, Harvinder; Singh, Ramandeep; Singh, Rupinder (Asian Review of Mechanical Engineering, 2016)
Die wear is an undesired and unpredictable failure and downtime reason in metal forming operations. It directly affects the part formability and surface quality, and causes production loss, cost increase and delays. In sheet metal stamping, the wear of deforming dies continues to be a great concern to the automotive industry as a result of increasing die maintenance cost and scrap rate. The demand to reduce the use of lubricants and increase tool life in sheet metal stamping has resulted in increased research on the suitable combination of die materials. During production, the higher forming forces, higher wear; galling and premature die surface failures, and eventually insufficient product quality, interrupted production, and unexpected cost increases. Hence, in order to prolong the die-life, reduce down-time, and increase production rate and profitability; manufacturers are looking into alternative die materials, coatings, lubricants and their compatible combinations that would increase the die-life/ performance at reasonable cost levels. There are so many options and combinations of die materials and coatings that it is rather time-consuming to select a proper, if not optimal, pair of die material and coating for a given application. The various types of tool or die steels are there which are used in industries like sheet metal industry and press working. The wear of tools or dies is a common problem in these industries. Hence the present study aims to investigate the wear performance of AISI D3 die steel against mild steel under dry sliding conditions. Sliding parameters such as sliding speed, sliding time and normal load are taken.